PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI MIA 2 SMAN 1 PEKANBARU - Roudhotul Fitria; Erviyenni '; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The successful achievement of learning can be helped byusing instructional media. Besides being able to convey information moreeasily, interesting media can motivate students to be more enthusiastic inlearning activities. Audio-visual media is a medium that communicates it’smessage can be received by hearing and sight, for example, the media film,voice slides, animation and computer-based multimedia. This study aims todetermine the increase in motivation, activity and learning outcomes ofstudents in class XI MIA 2 SMAN 1 Pekanbaru using classroom actionresearch conducted in two cycles. Each cycle consists of two meetingswhich includes four stages of implementation, namely: planning, action,observation, and reflection. Data collection included questionnaire,obervation and tests. The results showed that the percentage of studentsincreased activity and achieving the success criteria. The percentage ofstudent activity in the first cycle of 61.18% with categorized well and thesecond cycle of 82.87% were categorized as excellent. Percentage oflearning outcomes is also seen from mastery learning that enhances andhave achieved success criteria. Motivation of student gained average of59,09 with high motivation criteria. The percentage of mastery learningstudents in the first cycle only reached 76.47%, which has not reached thecriteria of success, while in the second cycle students learning completenesspercentage of 100% has achieved succes criteria. Based on the resultsobtained, it can be concluded that the use of audio-visual media canenhance the activity and student learning outcomes.Keyword: Media Audio visual, activities, learning outcomes